ISLAMIC LAW LEGISLATION IN AN EFFORT TO REFORM INDONESIA’S NATIONAL LAW - Sofyan; Sultan, Lomba; Musyahid, Achmad; Jaki Asti, Mulham (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2022)
The implementation of Islamic law in Indonesia is still in a phase of gaps and contradictions. In line with developing a national legal system, it is expected to uphold the rule of law based on justice and truth from prevailing values, culture, and community beliefs. In order to answer the related issues, this study applied a library research model based on relevant library materials in the form of books, journals, or related articles. The results of this study showed that the position of Islamic law in the legal system in Indonesia was equal to Western law and customary law as a source of national law formation. Islamic law as a legal order guided by the majority of the Indonesian Muslim society had lived and existed in the legal system of state administration through sharia-based legislation (Islamic law). However, it was undeniable that the implementation of Islamic law and the presence of sharia-based laws experienced a dilemma internally and externally, influenced by epistemological, methodological, and socio-cultural aspects of politics. In addition, the efforts to develop and foster national law integrated a legal system that was harmoniously structured and followed the needs and developments of community culture. Moreover, it provided a great opportunity to consciously place Islamic law into a complete source of national law shaded by The Five Principles and the 1945 Constitution without causing contradictory and problematic assumptions by relying on the principles of forming the people in perfect and unanimous unity. Finally, it took the middle way, could develop and move, and had the life force in forming itself according to the development and or progress of the times.